Peran Dinas Tenaga Kerja dalam Mengawal Perekonomian Masyarakat Melalui Upaya Peningkatan Kesejahteraan Pekerja dan Hak Atas Upah yang Layak di Kabupaten Pati Berdasarkan Perspektif Islam - Muzayyidatul Habibah (UIN Mahmud Yunus Batusangkar, 2022)
This study aims to determine: 1). The role of the labor service in overseeing the community's economy through efforts to improve the welfare of workers in Pati district 2). The role of the labor service in overseeing the community's economy through efforts to increase the right to decent wage for workers in Pati district. This research uses qualitative research methods with the type of approach used is field research Data collection used observation and interviews. The results showed that 1). The government of the manpower office in the field of industrial relations always monitors and coordinates by visiting companies, where companies must be able to provide welfare services and facilities for workers both for work interests and in terms of muamalah.2). The role of the labor service in efforts to increase the right to a decent wage for workers includes conducting coaching and monitoring and monitoring.